Semi-Automated Analysis of 4D Flow MRI to Assess the Hemodynamic Impact of Intracranial Atherosclerotic Disease - Vali, Alireza (Magn Reson Med, 2019)
PURPOSE: This study evaluated the feasibility of using 4D flow MRI and a semi-automated analysis tool to assess the hemodynamic impact of intracranial atherosclerotic disease (ICAD). The ICAD impact was investigated by evaluating pressure drop (PD) at the atherosclerotic stenosis and changes in cerebral blood flow distribution in patients compared to healthy controls. METHODS: Dual-venc 4D flow MRI was acquired in 25 healthy volunteers and 16 ICAD patients (ICA, n=3; MCA, n=13) with mild (<50%), moderate (50–69%), or severe (>70%) intracranial stenosis. A semi-automated analysis tool was developed to quantify velocity and flow from 4D flow MRI and to evaluate cerebral blood flow redistribution. PD at stenosis was estimated using the Bernoulli equation. The PD calculation was examined by an in-vitro phantom study against flow simulations. RESULTS: Flow analysis in controls indicated symmetry in blood flow rate (FR) and peak velocity (PV) between the brain hemispheres. For patients, PV in the affected hemisphere was significantly (65%) higher than the normal side (P=0.002). However, FR to both hemispheres of the brain was the same. The PD depicted significant correlation with PV asymmetry in patients (ρ=0.67 and P=0.02), and it was significantly higher for severe compared to moderate stenoses (3.73 vs 2.30 mmHg, P=0.02). CONCLUSION: 4D flow MRI quantification enables assessment of the hemodynamic impact of ICAD. The significant difference of the PD between patients with severe and moderate stenosis and its correlation with PV asymmetry suggests that PD may be a pertinent hemodynamic biomarker to evaluate ICAD.